THE EUROPEAN NIGHT OF MUSEUMS IN WARSAW – A RESEARCH COMMENTARY - Bojanowska, Elżbieta (Uniwersyteckie Czasopismo Socjologiczne, 2016)
The team of the Research Laboratory of the Polish Measurement of Attitudes and Values (PPPiW) already for the fourth time measured the participation in the European Night of Museums in Warsaw. The research was conducted during the night of 16th to 17th of May 2015. The sample was N = 1,102 respondents varied in terms of gender, age, education, place of residence and income. 20 museums, located in different districts, were selected for the research, which enabled the spatial stratification of the sample. The research commentary refers to the following issues of communing with culture: the frequency of reaching for the sources of knowledge about it, the frequency of visiting facilities being its vehicle, and readership. At the same time, it needs to be said that participation in culture refers mainly to its passive consumption, namely by means of the cinema and television. Therefore, the source of knowledge about art lies in the image which supersedes the traditional role of text. Participation in culture becomes a characteristic feature of more and more narrow, elite social group. Participation in high culture to a greater and greater extent becomes the measure of social distances. It leads to the deepening of socio-cultural distances between the groups with higher positions and less educated social groups, also between the residents of cities and villages.